Kedudukan Ahli Waris yang Pindah Agama menurut Hukum Waris Adat Bali di Desa Dangin Tukadaya Kabupaten Jembrana - I Putu Endar Pranata; I Ketut Sukadana; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2020)
The issue of changing religions related to inheritance based on Balinese customary law is a very important matter. In the customary norms of inheritance in Bali, inheritance is a system of transferring responsibility from one generation to the next. This responsibility goes with the attachment of a right. This responsibility includes responsibilities within the indigenous community. This research was conducted with the aim of describing how the kinship relationship of a son who converted and how the position of an heir who converted according to Balinese traditional inheritance law in Dangin Tukadaya Village, Jembrana Regency. This research employed empirical legal research with a sociology of law approach. The results of this research showed that the kinship of a son who converted is still close to their families. The conversion of religion does not break the kinship relationship, but its rights and obligations are no longer related to Sanggah Desa Adat and Pura Desa for having committed an act of disobedience. In addition, the position of a heir who changed religion according to Balinese traditional inheritance law in Dangin Tukadaya Village, Jembrana Regency is no longer an heir because he has no relationship with Sanggah Desa Adat and Pura Desa and has become a disobedient person.